BIOBJECTIVE MODEL FOR REDESIGNING SALES TERRITORIES - Correa, Juan Gabriel (International Journal of Industrial Engineering: Theory, Applications and Practice, 2012)
<span style="font-size: 10.0pt; line-height: 115%; font-family: "Times New Roman","serif"; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-bidi-theme-font: minor-bidi; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">Designing and updating of sales territories are strategic activities that have several causes like mergers and changes in the markets among others. The new territories must satisfy the planning characteristics defined by each company. In this paper we propose a biobjective mixed integer programming model for redesigning sales territories. The study was motivated by the case of a company that distributes its products along Mexico. The model looks for minimizing the total sum of the distances and the variation of the sales volumes for each salesman with respect to the current situation. The model is solved using the <span style="font-size: 10.0pt; line-height: 115%; font-family: "Times New Roman","serif"; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-bidi-theme-font: minor-bidi; mso-ansi-language: ES-MX; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">ε<span style="font-size: 10.0pt; line-height: 115%; font-family: "Times New Roman","serif"; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-bidi-theme-font: minor-bidi; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">-constraint method to obtain the true efficient set, and a heuristic method to obtain the approximate efficient set. Both efficient sets are compared to determine the quality of solutions obtained by the heuristic method.